Chronology of Key Events of Riga Technical University in Study Year 2019/2020 - Gudro, Ilze; Lapsa, Rūta; Zigmunde, Alīda (History of Engineering Sciences and Institutions of Higher Education, 2020)
In study year 2019/2020